1988
DOI: 10.1111/j.1600-065x.1988.tb00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Possible Involvement of CTL Granule Proteases in Target Cell DNA Breakdown

Abstract: We have carried out experiments to test whether the granule exocytosis model for lymphocyte cytotoxicity can account for the rapid target DNA breakdown seen during CTL-induced cytotoxicity. Dense granules isolated from cloned mouse CTL and from rat NK tumor cells cause target DNA breakdown during granule cytolysin-mediated lysis of tumor cells, while the purified granule cytolysin caused lysis without DNA breakdown. When target cells are permeabilized with detergent, granule extracts have the ability to releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 23 publications
4
23
0
Order By: Relevance
“…In addition, they support the findings of Munger et al [43] demonstrating the presence of BLT esterase-and cytolysincontaining cytoplasmic granules in primary allo-immune peritoneal exudate T cells. However, these and the present data are contradicted by observations of Berke and Rosen [20] and Dennert et al [21].…”
Section: Discussionsupporting
confidence: 87%
“…In addition, they support the findings of Munger et al [43] demonstrating the presence of BLT esterase-and cytolysincontaining cytoplasmic granules in primary allo-immune peritoneal exudate T cells. However, these and the present data are contradicted by observations of Berke and Rosen [20] and Dennert et al [21].…”
Section: Discussionsupporting
confidence: 87%
“…LGLs correspond to a heterogenous cell population including NK cells, cytotoxic T lymphocytes (CTLs) and lymphokine-activated killer (LAK) cells (KANEDA, 1989). Cytoplasmic granules of the lymphocytes contain cytotoxic substances including perforin (PODACK et al, 1985), a family of serine esterases (MUNGER et al, 1988;HAYES et al, 1989;ZUNINO et al, 1990), and TIA-1 (TIAN et al, 1991) as effector molecules which kill target cells.…”
Section: Lymphocyte-induced Apoptosis Of Enterocytes In the Guinea Pigmentioning
confidence: 99%
“…There is ample evidence from in vitro studies that CTL/NK cell-mediated nuclear DNA breakdown (apoptosis) and death of tumor cells is critically dependent on granule exocytosis [3] and the simultaneous activation of perforin (perf) and granzymes (gzm) [4][5][6][7][8]. In fact, by using purified native material from mouse CTL or rat NK cell lines it was found that perf alone was able to induce 51 Cr release in target cells, but that substantial DNA fragmentation of the same cells only occurred with a combination of perf and gzm [4,6,7].…”
Section: Introductionmentioning
confidence: 99%